Uncertainty underground : Yucca Mountain and the nation's high-level nuclear waste - Macfarlane, Allison; Ewing, Rodney C. (MIT Press, 2006)
"Despite approval by Congress and the Bush administration and over seven billion dollars already spent, the Yucca Mountain, Nevada, site for disposal of highly radioactive spent nuclear fuel is not yet in operation. The reasons for the delay lie not only in citizen and activist opposition to the project but also in the numerous scientific and technical issues that remain unresolved. Although many scientists favor geologic disposal of high-level nuclear waste, there are substantial unknowns in projecting the performance of a site over the tens to hundreds of thousands of years that may be required by Environmental Protection Agency standards. Uncertainty Underground is the first effort to review the uncertainties in the analysis of the long-term performance of the proposed repository at Yucca Mountain. The book does not pass judgment on the suitability of the site but provides reliable science-based information to support open debate and inquiry into its safety. Experts from the geosciences, industry, and government review different aspects of the repository system, focusing on the uncertainties inherent in each. After an overview of the historical and regulatory context, the contributors investigate external factors (including climate change and volcanic activity) that could affect repository performance and then turn to topics concerning the repository itself. These include hydrologic issues, the geological conditions with which the nuclear waste in the repository would interact, and the predicted behavior of the different kinds of waste and waste package materials. Uncertainty Underground succeeds in making these important technical issues understandable to a wide audience, including policymakers and the general public"--Publisher's description